2018
DOI: 10.30849/rip/ijp.v52i2.491
|View full text |Cite
|
Sign up to set email alerts
|

Repertorio socio-psicológico del conflicto colombiano en el discurso presidencial de Juan Manuel Santos

Abstract: El presente estudio buscó analizar el discurso del presidente de Colombia Juan Manuel Santos durante su primer mandato (2010-2014) cuando comenzaron los diálogos de paz entre el Gobierno y las FARC-EP. Para ello se emplearon los métodos unidimensional y multidimensional de estadística lexicometrica buscando caracterizar los pronunciamientos a partir de las variables tipo de audiencia (nacional vs. internacional) y momento de emisión (antes vs. después del inicio de los diálogos). Apelaciones a la esperanza rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Instead, ex-combatants' former group membershipmainly guerrillas and paramilitary groups-was usually considered and often analyzed as an explanatory variable in psychosocial processes. Both guerrilla and paramilitary demobilized participants in these studies were involved in state-led rehabilitation or reintegration programs, notably by the Colombian Agency for Reintegration (López-López, Rincón-Unigarro, et al, 2018;Trujillo et al, 2017;Ugarriza & Craig, 2013;Ugarriza & Nussio, 2017). Some of the psychosocial processes studied in this body of research include a sentiment of reconciliation, empathy, and ideology.…”
Section: Former Perpetrators Of Violencementioning
confidence: 99%
See 4 more Smart Citations
“…Instead, ex-combatants' former group membershipmainly guerrillas and paramilitary groups-was usually considered and often analyzed as an explanatory variable in psychosocial processes. Both guerrilla and paramilitary demobilized participants in these studies were involved in state-led rehabilitation or reintegration programs, notably by the Colombian Agency for Reintegration (López-López, Rincón-Unigarro, et al, 2018;Trujillo et al, 2017;Ugarriza & Craig, 2013;Ugarriza & Nussio, 2017). Some of the psychosocial processes studied in this body of research include a sentiment of reconciliation, empathy, and ideology.…”
Section: Former Perpetrators Of Violencementioning
confidence: 99%
“…Some of the psychosocial processes studied in this body of research include a sentiment of reconciliation, empathy, and ideology. López-López, Rincón-Unigarro, et al (2018) found that a majority of ex-combatants reported high levels of a sentiment of reconciliation-that is, the individual feeling of being personally reconciled with those whom they offended in the past (Mukashema & Mullet, 2010). However, ex-combatants who did not participate in rehabilitation programs had smaller support networks, and former guerrilla combatants-as opposed to former paramilitary combatants-scored lower on the sentiment of reconciliation scale (López-López, Rincón-Unigarro, et al, 2018).…”
Section: Former Perpetrators Of Violencementioning
confidence: 99%
See 3 more Smart Citations